Strengthening Social and Emotional Intelligences Through Writing - Burth, Jeanne Hager; McConnell, Michelle (Journal of the American Academy of Special Education Professionals, 2017)
Using writing to allow children with Autism Spectrum Disorder (ASD) to express how they are feeling or to stimulate thinking about a social situation will allow the students the opportunity to strengthen social and emotional intelligences. By giving prompts about different social and emotional situations or ideas to children, the teacher allows the children to think about social circumstances and get used to new ways of thinking. Prompts may be associated with scenarios and followed by questions, such as "How would this make me feel?" or "How do you think the other person feels? How do you know?" By responding to the prompts, the students should be thinking more about their own emotions and about how the other person feels, along with what may have changed the situation. By using writing as a response to the prompts, students who have difficulty communicating will have the opportunity to be thoughtful about their responses before actually acting or reacting in a real situation.